2015
DOI: 10.1155/2015/916902
|View full text |Cite
|
Sign up to set email alerts
|

Garcinia dulcisFruit Extract Induced Cytotoxicity and Apoptosis in HepG2 Liver Cancer Cell Line

Abstract: Garcinia dulcis or locally known in Malaysia as “mundu” belongs to the family of Clusiaceae. The study was conducted to investigate the anticancer potential of different parts of G. dulcis fruit extracts and their possible mechanism of action in HepG2 liver cancer cell line. MTT assay showed that the peel, flesh, and seed extracts of G. dulcis induced cytotoxicity in HepG2 cell line with IC50 values of 46.33 ± 4.51, 38.33 ± 3.51, and 7.5 ± 2.52 µg/mL, respectively. The flesh extract of G. dulcis induced cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…It has been reported that H 2 O 2 caused the targeted oxidation of cellular molecular leading to mutagenesis and death of cell (García‐Nebot et al, ). The Sub‐G1 phase is a fragment present before the G0/G1 phase, and the increase in sub‐G1 phase was a reflection of apoptosis induction (Abu Bakar, Ahmad, Suleiman, Rahmat, & Isha, ). The treatment with the component I, II, III, IV, and F5000 on injury cells could prevent the reduction in the proportion of cells in G1 phase and the rise in sub‐G1 phase induced by oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that H 2 O 2 caused the targeted oxidation of cellular molecular leading to mutagenesis and death of cell (García‐Nebot et al, ). The Sub‐G1 phase is a fragment present before the G0/G1 phase, and the increase in sub‐G1 phase was a reflection of apoptosis induction (Abu Bakar, Ahmad, Suleiman, Rahmat, & Isha, ). The treatment with the component I, II, III, IV, and F5000 on injury cells could prevent the reduction in the proportion of cells in G1 phase and the rise in sub‐G1 phase induced by oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Based on DPPH (2,2diphenyl-1-picrylhydrazyl) assays, a variety of phenolic compounds obtained from the flower, fruit, and seed parts exhibited radical scavenging activity. Ten µM each of quercetin 3-O-βgalactopyranoside (30), fukugeside (32), xanthochymol (34), and guttiferone E (37) from the flowers showed potent antioxidant activity producing scavenging values of 57%, 56%, 60% and 59%, respectively, whereas that of the reference anti-oxidant, butylated hydroxytoluene (BHT) was only 43% [21]. Among the 42 compounds isolated from the green and ripe fruits, morelloflavone (1), camboginol (52), dulcisflavan (69), cambogin (79), and (-)epicathechin (81) were effective scavengers of the DPPH radical.…”
Section: Anti-oxidant Activitymentioning
confidence: 99%
“…When the peel, flesh and seed extracts of G. dulcis fruit were tested against the HepG2 liver cancer cell line in MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay, they induced cytotoxicity to the cells with IC 50 values of 46.3, 38.3 and 7.5 µg/mL, respectively. Moreover, the flesh extract, which contains hydroxymethylfurfural and 3-methyl-2,5-furandione as the main components, showed its potential as a liver cancer chemotherapeutic agent by inducing apoptosis in HepG2 cells [32]. Two hydroxyxanthones, 2-(1,1-dimethyl-allyl)-1,4,5-trihydroxyxanthone (12b-hydroxy-des-D-garcigerin) (95) and 4-(1,1-dimethyl-allyl)-1,2,5-trihydroxyxanthone (globuxanthone) (117), isolated from the bark exhibited remarkable anti-androgenic effects by inhibiting androgen receptor transcription in prostate cancer LNCaP cells as compared with bicalutamide, a non-steroidal anti-androgen used primarily in the treatment of prostate cancer [33].…”
Section: Anti-cancer/tumor Activitymentioning
confidence: 99%
“…The crushed fruit is used as an expectorant to clear sputum, alleviate cough, treat scurvy and as a mild laxative [2,5,6]. An extract of G. dulcis fruit showed hepatoprotective and anti-proliferative properties [7,8].…”
Section: Introductionmentioning
confidence: 99%